The Presence of Parties in the Drafting of Notarial Deeds in the Digital Era: A Comparative Legal Study in Indonesian (Lembaga Contrarius Indonesia, 2026)
The digitalization of contract law and public services challenges traditional notarial practice, especially the rule that parties must be physically present before a notary when executing authentic deeds. Indonesia’s Electronic Information and Transactions Law (E-IT Law) recognizes the legal validity of electronic documents and signatures, yet the Notary Office Law still presumes in-person appearances. This normative-comparative study analyzes Indonesian instruments (Notary Office Law, E-IT Law, and Personal Data Protection Law) and compares e-notarization approaches in the Netherlands, Singapore, and Malaysia. We find that Indonesia’s physical-presence model is misaligned with the E-IT Law’s recognition of secure electronic documents. Dutch emergency measures during COVID-19 demonstrated that remote notarial acts can be institutionalized with safeguards in place. Singapore and Malaysia provide technologically neutral e-signature frameworks that support remote identification, robust audit trails, and data protection. We recommend amending the Notary Office Law to recognize an online presence as the functional equivalent of physical presence, provided that identity assurance, integrity, auditability, and data protection are satisfied.